2016
DOI: 10.1136/bmjopen-2015-010889
|View full text |Cite
|
Sign up to set email alerts
|

Change in fasting plasma glucose and incident type 2 diabetes mellitus: results from a prospective cohort study

Abstract: ObjectiveTo investigate the association between changes in fasting plasma glucose (FPG) values and incident type 2 diabetes (T2D) in a cohort of the Iranian population.DesignProspective cohort study.SettingThis study was conducted within the framework of the Tehran Lipid and Glucose Study (TLGS) to investigate the association between change in FPG between baseline examination (1999–2001) and the second visit (2002–2005) with incident T2D.ParticipantsA total of 3981 non-diabetic participants aged ≥20 years.Outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Fasting plasma glucose (FPG), 2-h plasma glucose, triglycerides (TG), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C) levels were measured according to the standard protocols 34 . Type 2 diabetes was diagnosed based on the fasting plasma glucose ≥ 126 mg/dL or 2-h plasma glucose ≥ 200 mg/dL during an oral glucose tolerance test 35 . The first occurrence of type 2 diabetes in individuals during the follow-up period was considered as diabetic condition 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Fasting plasma glucose (FPG), 2-h plasma glucose, triglycerides (TG), total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), and low-density lipoprotein cholesterol (LDL-C) levels were measured according to the standard protocols 34 . Type 2 diabetes was diagnosed based on the fasting plasma glucose ≥ 126 mg/dL or 2-h plasma glucose ≥ 200 mg/dL during an oral glucose tolerance test 35 . The first occurrence of type 2 diabetes in individuals during the follow-up period was considered as diabetic condition 36 .…”
Section: Discussionmentioning
confidence: 99%
“…Since the TLGS is a longitudinal cohort with repeated measurements for exposures, it gave us the opportunity to investigate the effect of changes of risk factors on outcomes. For instance, we demonstrated that the three-year increase in systolic and diastolic blood pressure were associated with increased risk of CVD independently (29); or this rise in fasting plasma glucose could help identify high risk populations for incident type 2 diabetes, independent of important traditional risk factors (30). We also showed the effect of changes in anthropometric measures on the incidence of diabetes, CVD and total mortality (23, 31, 32).…”
Section: Resultsmentioning
confidence: 99%
“…Elevated FPG level has been comprehensively investigated as a core component in models for risk assessment of T2D 19,20 . Analysis of the Tehran Lipid and Glucose Study showed a positive association between changes in FPG levels and the incidence of T2D 21 . As expected, our results indicated that changes in FPG levels were most strongly associated with the development of T2D.…”
Section: Discussionmentioning
confidence: 97%